A city-scale assessment of emergency response accessibility to vulnerable populations and facilities under normal and pluvial flood conditions for Shanghai, China. (October 2021) - Yin, Jie; Yu, Dapeng; Liao, Banggu
This paper describes the development of a scenario-based approach that couples 2D hydrodynamic modeling with Geographic Information System (GIS) network analysis to assess the vulnerability of emergency services to surface water flooding at a large city scale. The method is demonstrated for Emergency Medical Service and Fire & Rescue Service in the city of Shanghai, China. Considering four representative traffic conditions, accessibility in terms of service area, response time, and population coverage within specified timeframes (8-, 12-, and 15-minute for Emergency Medical Service and 5-, 10-, and 15-minute for Fire & Rescue Service) is quantified and mapped under normal as well as pluvial flood scenarios of various magnitudes (5-, 20-, and 100-year return periods). Results show that the performance of operational responses largely depends on the functioning of transportation system, dramatically decreasing from unobstructed to congested traffic. Surface water flooding is found to result in limited (i.e. site-specific) but nonlinear impacts on the city-wide emergency service provisions. The results provide detailed information for optimizing the distribution of emergency stations and developing strategic contingency planning for vulnerable populations and facilities.